Pharmacokinetics and pharmacodynamics across infusion rates of intravenously administered nipocalimab: results of a phase 1, placebo-controlled study - Leu, Jocelyn H.; Vermeulen, An; Abbes, Claudia; Arroyo, Santiago; Denney, William S.; Ling, Leona E. (Frontiers in Neuroscience, 2024)
Introduction Nipocalimab is a high-affinity, fully human, aglycosylated, effectorless, immunoglobulin G (IgG) 1 monoclonal antibody that targets the neonatal Fc receptor (FcRn), decreases systemic IgG including autoantibodies, and is under development in several IgG autoantibody- and alloantibody-mediated diseases, including generalized myasthenia gravis, chronic inflammatory demyelinating polyneuropathy, maternal-fetal medicine, and multiple other therapeutic areas. An initial phase 1 study with single and multiple ascending doses of nipocalimab infused intravenously (IV) over 2 h demonstrated dose-dependent serum pharmacokinetics and IgG reductions, with an adverse event (AE) profile comparable to placebo. Methods The current investigation evaluates the safety, tolerability, pharmacokinetics, and pharmacodynamics of single doses of nipocalimab across various IV infusion rates in a randomized, double-blind, placebo-controlled, sequential-dose study. Forty participants were randomized to receive nipocalimab 30 mg/kg over 60, 30, 15 or 7.5 min (0.5, 1, 2, or 4 mg/kg/min); nipocalimab 60 mg/kg over 15 min (4 mg/kg/min); or matching placebo. Results At doses up to 60 mg/kg and infusion rates up to 4 mg/kg/min (maximum clinically feasible rate), single doses of nipocalimab were tolerable, with 12 (40%) participants experiencing AEs across nipocalimab cohorts compared with 1 (10%) participant in the placebo cohort. AEs deemed treatment related occurred in 6 (20%) participants receiving nipocalimab and 1 (10%) participant receiving placebo. None of the AEs were severe, and no participants discontinued treatment due to AEs. Nipocalimab provided consistent, dose-dependent serum pharmacokinetics and IgG reductions, regardless of infusion rate. Discussion This study supports the use of shortened durations of nipocalimab infusion for future studies.